c - d (b, 2017)
Reminiscences of A. M. A. Muhith, born in 1934, politician and economist from Bangladesh.
In Bengali.
Keywords: Muhith, A. M. A., -- 1934-; Politicians -- Bangladesh -- Biography; Economists -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-; Bangladesh -- Biography